2019
DOI: 10.2319/020118-93.1
|View full text |Cite
|
Sign up to set email alerts
|

A 15-year follow up of an orthodontic treatment including a lower incisor extraction and keeping the maxillary canine–premolar transposition

Abstract: Lower incisor extraction is an effective option for treating lower anterior crowding in patients with a good facial profile, Class I molar occlusion, and narrow upper incisors. This report describes the successful treatment of an adolescent patient with lower anterior crowding and a transposed maxillary canine and premolar treated by extracting a lower incisor and keeping the transposed positions of the teeth. With the use of retainers, treatment results were stable up to the 2-year postretention visit. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the literature survey performed during this study, 12 articles reported an association between TT and agenesis 3,4,9,11,13,14,17,20,54,55,62,64 but none described the occurrence of tooth giroversion. The reported frequency of the association between TT and agenesis in previous studies was around 37-40% 16,65 .…”
Section: Discussionmentioning
confidence: 92%
“…In the literature survey performed during this study, 12 articles reported an association between TT and agenesis 3,4,9,11,13,14,17,20,54,55,62,64 but none described the occurrence of tooth giroversion. The reported frequency of the association between TT and agenesis in previous studies was around 37-40% 16,65 .…”
Section: Discussionmentioning
confidence: 92%
“…21 The transposition between a canine and the first premolar teeth warrants that treatment alternatives with or without extraction be fully considered and discussed. 22,23 The extraction of either all first premolars or the transposed premolar might be valid options. In a non-extraction approach, the teeth may either be kept in the transposed position or aligned in the correct order.…”
Section: Discussionmentioning
confidence: 99%
“…The view on stability appears controversial as contradictory statements were found, with some reporting stable results, 7 , 16 - 18 while others reported instability and promoted the need for long-term retention. 19 The presence of lingually bonded retainers resulted in less relapse than in patients without a retainer. 20 …”
Section: Introductionmentioning
confidence: 97%